2000
DOI: 10.1038/35016618
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of enteropathogenic Escherichia coli intimin–receptor complex

Abstract: Intimin and its translocated intimin receptor (Tir) are bacterial proteins that mediate adhesion between mammalian cells and attaching and effacing (A/E) pathogens. Enteropathogenic Escherichia coli (EPEC) causes significant paediatric morbidity and mortality world-wide. A related A/E pathogen, enterohaemorrhagic E. coli (EHEC; O157:H7) is one of the most important food-borne pathogens in North America, Europe and Japan. A unique and essential feature of A/E bacterial pathogens is the formation of actin-rich p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
313
0
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(334 citation statements)
references
References 27 publications
14
313
0
7
Order By: Relevance
“…Different types of Tir proteins have also been described. Since the interaction between intimin and Tir is located in the 280 carboxy terminal amino-acids of the intimin adhesin, the different intimin types specifically interact with their cognate Tir receptor Hartland et al, 1999;Luo et al, 2000;Karmali et al, 2010;Schmidt, 2010). Alternative host receptors for the intimin adhesin are ␤1 integrins and nucleolin (Garmendia et al, 2005).…”
Section: Outer Membrane Proteins (Omps)mentioning
confidence: 99%
“…Different types of Tir proteins have also been described. Since the interaction between intimin and Tir is located in the 280 carboxy terminal amino-acids of the intimin adhesin, the different intimin types specifically interact with their cognate Tir receptor Hartland et al, 1999;Luo et al, 2000;Karmali et al, 2010;Schmidt, 2010). Alternative host receptors for the intimin adhesin are ␤1 integrins and nucleolin (Garmendia et al, 2005).…”
Section: Outer Membrane Proteins (Omps)mentioning
confidence: 99%
“…The solution (Kelly et al , 1999) and crystal (Luo et al , 2000) 3D structure of Int280 α revealed that the polypeptide comprises a series of three globular modules with a distinct organization. The two domains (D1–2) closest to the bacterial cell surface comprise β -sheet sandwiches and structurally resemble immunoglobulin (Ig)-like folds.…”
Section: Introductionmentioning
confidence: 99%
“…Tir is one of the virulence factors termed "effectors," which are delivered directly into the host cytoplasm through bacterial secretion machinery termed the type III secretion system (TTSS) (24,46). The secreted Tir is in turn integrated into the plasma membrane and binds with a bacterial outer membrane protein, intimin (31). The binding induces the clustering of the membrane-associated Tir beneath the bacteria, which activates an Nck adaptor molecule at the cytoplasmic face of the plasma membrane and finally results in activation of neural Wiskott-Aldrich syndrome protein (N-WASP) and the downstream actin-nucleating Arp2/3 complex (19,23).…”
mentioning
confidence: 99%